2022
DOI: 10.1002/hed.27283
|View full text |Cite
|
Sign up to set email alerts
|

Development of machine learning models for the prediction of positive surgical margins in transoral robotic surgery (TORS)

Abstract: Purpose To develop machine learning (ML) models for predicting positive margins in patients undergoing transoral robotic surgery (TORS). Methods Data from 453 patients with laryngeal, hypopharyngeal, and oropharyngeal squamous cell carcinoma were retrospectively collected at a tertiary referral center to train (n = 316) and validate (n = 137) six two‐class supervised ML models employing 14 variables available pre‐operatively. Results The accuracy of the six ML models ranged between 0.67 and 0.75, while the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…Costantino et al [ 13 ] developed and validated six ML prediction models to predict the risk of surgical positive margins in patients who underwent transoral robotic surgery (TORS). In particular, the authors found that tumour classification and tumour site are the most important predictors of positive surgical margins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Costantino et al [ 13 ] developed and validated six ML prediction models to predict the risk of surgical positive margins in patients who underwent transoral robotic surgery (TORS). In particular, the authors found that tumour classification and tumour site are the most important predictors of positive surgical margins.…”
Section: Resultsmentioning
confidence: 99%
“…The author conducted this systematic review following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines [12] as reported in Figure 1. The authors searched all papers in the three major medical databases, such as Scopus (Elsevier), PubMed [National Institutes of Health's National Library of Medicine (NLM NIH)], and Cochrane Library (Wiley).…”
Section: Methodsmentioning
confidence: 99%
“…To date, however, relatively few studies have investigated the role of AI in TORS. For example, only two studies have evaluated the value of AI (machine learning) to assess surgical margins following tumour resection with TORS 6,7 . Nevertheless, given the promising findings of those studies, more research is clearly warranted.…”
Section: Robotic Surgerymentioning
confidence: 99%
“…AI has the potential to improve head and neck surgery in many different ways, but especially by improving the analysis of medical imaging, voice samples, gene expression and clinical data 4 . AI can be applied in a wide range of different areas, including robotic surgery, 5–8 radiotherapy, 9,10 clinical oncology, 11 radiology, 12–17 nursing, 18–20 pathology, 6,21–23 phoniatrics 24 and molecular biology 25–28 . AI has been used to develop prediction models based on the analysis of existing data sets to predict cancer progression, 29 overall survival stratification, 30 lymph node metastases, 31,32 treatment‐related toxicity 11 and hospital stay length 33 .…”
Section: Introductionmentioning
confidence: 99%
“…It provides improved precision, dexterity, and visualization, enabling surgeons to perform complex operations with greater accuracy and control. Andrea et al [150] propose the utilization of machine learning models to tackle the challenge associated with the prediction of positive surgical margins in patients subjected to transoral robotic surgery (TORS). Positive surgical margins have been linked to unfavorable clinical outcomes, emphasizing the importance of preoperative identification of patients at risk.…”
Section: ) Roboticsmentioning
confidence: 99%